Scottish trade with Africa and the West Indies in the early 18th century, 1694-1709. (East Ardsley, Wakefield, United Kingdom : Microform Academic Publishers, 2009)
The Company of Scotland Trading to Africa and the Indies, better known as the Darien Company, was created by Act of the Scots Parliament on 26 June 1695, receiving royal assent from King William II of Scotland (William III of England), almost 100 years after the 'Union of the crowns'. The intention was for Scotland set up trading colonies around the globe after the model of other European nations at that time, beginning with a settlement on the Darien Isthmus near present-day Panama. This BRRAM collection includes all the principal manuscripts at the National Library of Scotland on the doomed scheme, and complements the earlier published collection of documents held in the archives of the Royal Bank of Scotland (RBS). While the bulk of these papers date from 1696 through to 1707, including copies of the general journals for the Company, the collection also contains certain miscellaneous documents which antedate by two years the legal incorporation of the Company, and others that span the period of its dissolution up to 1709. The quality and variety of financial documents and in the amount of correspondence are remarkable, the bulk dating from the initial period to 1700, culminating in the return of survivors from the second disastrous expedition to Darien. Among the former category are numerous subscription books, dating from 1696. In addition there are account books, detailed cash books and receipts, trading ledgers and promissory notes, the book of the Company's store & warehouse keeper at the port in Leith, together with lists of goods shipped. The minute books and journals of the principal of the Company's committees also survive. The enterprise was motivated by the desire to invigorate an ailing Scottish economy and, at the same time, to compete with the Honourable East India Company, established in England in 1600. However, the massive debts incurred as a result of the collapse of this initiative in 1699 were perhaps the chief factor which drew Scotland into the 'Act of Union' of 1707. As such, these manuscripts are significant not only to the study of British trade with the Americas in the late 17th century, but also the sweeping political and economic changes that gave rise to the forging of Great Britain. In addition, they provide a detailed and comprehensive, yet manageable, record of the systems and processes by which European colonisation and trade might be spread. Accompanied by an online guide to the collection.
Date range: 1694-1709.
Keywords: Scotland -- Commerce -- Africa -- History -- 18th century; Scotland -- Commerce -- West Indies -- History -- 18th century